Determinants Of Banking Efficiency For Commercial Banks In Indonesia: Two-Stage Data Envelopment Analysis - Desmy Riani; Denia Maulani (Fakultas Ekonomi, Universitas Bangka Belitung, 2021)
This study measured and analyzed the determinants of banking efficiency for commercial banks in Indonesia using the Two-Stage Data Envelopment Analysis approach within 2015-2019 period. The object in this study is commercial banks which are included in the group 4 banks category consisting of 7 conventional commercial banks. The first stage measured level of bank efficiency by Data Envelopment Analysis (DEA). BNI in 2015 and BCA during the period 2015 to 2019 shows inefficient on managing the resources. The second stage is analyzed the factors that have an influence in achieving the level of bank efficiency using the Tobit model which shows that Operational Cost and Operational Revenue (BOPO), Return on Equity (ROE), Return on Assets (ROA), and Non Performing Loans (NPL) have a significant effect on bank efficiency. Meanwhile, the Capital Adequacy Ratio (CAR) and the Loan to Deposit Ratio (LDR) have no significant impact on bank efficiency.